Pengaruh Saluran Distribusi, Harga dan Kualitas Produk terhadap Keputusan Pembelian Alat Kesehatan Merek Human pada PT. Media Diagnostika Surabaya - Wahyu Nur Syahidin; Ony Kurniawati; Baramadya Baramadya (Jurnal Simki Economic, 2024)
This study aims to analyze the influence of distribution channels, price, and product quality on the purchasing decisions of Human brand medical equipment at PT. Media Diagnostika Surabaya. The research method is quantitative with descriptive analysis, involving 80 respondents selected through accidental sampling. Respondents consist of consumers from various sectors such as hospitals, clinics, laboratories, and companies purchasing Human brand medical equipment. Partial test analysis shows that distribution channels, price, and product quality individually have a positive and significant impact on purchasing decisions. The simultaneous test results demonstrate a positive and significant contribution, indicating that the dependent variable is influenced by the independent variables together. The R² test results show that 69.6% of the variation in purchasing decisions is explained by these three factors, while 30.4% is influenced by other factors.